Modulação da expressão gênica e proteica caruncular pelo embrião bovino durante a placentação - Jesus, Carla Fabiana Gomes de (2015)
Despite the existence of several studies related to reproduction, some events about embryo loss in early gestation are not understand due the variables involved. This study aimed to identify differentially expressed genes between uterine caruncles of the gravid horns (G) and non-gravid horns (NG) horns during the bovine placentation and investigate the role of embryo produced by in vitro fertilization (IVF) in this gene expression. The finding that the embryo also influences the caruncular gene and protein expression could clarify which embryo signals that regulate uterine development and that the findings may be related to high failure rates of pregnancy in the pregnancies of manipulated embryos. In the present study caruncles from the G and NG were collected from pregnant primiparous cows (Bos indicus) undergoing artificial insemination (AI) or transfer of embryos produced by in vitro fertilization (IVF) using Bos indicus male sexed sperm. Animals were slaughter at 30 (n = 3), 35 (n = 8) or 40 (n = 3) days of gestation and tissues were collected following separation of the weakly associated cotyledons. Tissues were either frozen in liquid nitrogen or stored at -80°C freezer until RNA or protein extraction or fixed in 4% buffered formaldehyde for immunohistochemical analysis. The transcriptome of samples of 35 days (n = 7) were evaluated by microarray using an Affymetrix microarray platform. Analysis showed that 23.000 genes, 149 were differentially expressed in cattle caruncles from the gravid horn (≥ 1.5 fold, p<0.05). Nine genes potentially involved in cell differentiation were used to validate the results of real time PCR: seven upregulated genes (ACP5,DPP4, GJB6, IGFBP3, INHBA, STC1,THBS2) and two downregulated genes (CXCR4 e PTGS2). Quantitative PCR demonstrated that expression ratios of selected genes were consistent with the microarray results (p<0,05). Western blot analysis was performed to investigate PTGS2, THSB2 e IGFPB3. Densitometric evaluation indicated an increase in protein content of PTGS2 at 40 days and IGFPB3 and THSB2 at 35 ABSTRACT 4 and 40 days of IA both gestations. In FIV gestations, PTGS2 protein abundance was significantly higher at 35 days in caruncles from the gravid horn. On the other hand, the pattern of IGFPB3 e THSB2 protein expression in FIV gestations was similar to that observed in IA gestations. Protein immunostaining was observed in the cytoplasm of epithelial and stromal uterine cells, glandular uterine cells and endothelial uterine cells. We observed that staining intensity was associated to western blot data, with cells from cotyledon-associated caruncle showing more intensity of staining at 35 and 40 days in both AI and FIV gestations. We conclude that the expression of placentation involved genes differentially expressed in caruncles of pregnant and non-pregnant horns suffer influence of embryo and procedures such as in vitro embryo production and cell culture can influence the regulation of these molecules, since the greatest expression of most genes in IVF pregnancies occurred later after 40 days.